Development of a roadmap for Lean Six Sigma implementation and sustainability in a Scottish packing company. Issue 6 (14th May 2020) - Flor Vallejo, Verónica; Antony, Jiju; Douglas, Jacqueline Ann; Alexander, Paul; Sony, Michael
Abstract : Purpose: Lean Six Sigma (LSS) is a continuous improvement methodology that has been adopted by several companies as a strategy to increase their competitive advantage. However, due to the misuse of LSS theory in practice, a high rate of implementation failure results. There is a need for a structured and standardised framework to describe how the LSS initiative should be implemented and sustained over time. As a result, this study aims to develop a practical, user-friendly and accurate LSS road map for a Scottish manufacturing small and medium enterprise. Design/methodology/approach: The approach was to analyse existing literature on lean and Six Sigma that included road maps and critical success factors (CSFs) in order to design an in-company, quantitative survey instrument. The aim of the survey was to evaluate employees' perceptions on the importance of LSS CSFs for the successful implementation and sustainability of a continuous improvement initiative. Based on the literature and results from the data collected, an LSS reference guide - in the form of a road map - was designed to support LSS implementation and sustainability. Findings: A customised LSS reference guide in a road map format for the Scottish SME was proposed. This road map was developed by adopting existing successful road maps from the literature into consideration and then adapting them to fulfil the company's particular perspective on CI. This study complements current literature on LSS road maps and corroborates LSS CSFs as crucial for successful LSS implementation and sustainability, regardless of the type of company and/or culture. However, a degree of importance is ascribed to the organisation's culture. Research limitations/implications: Whilst a survey was used as the data collection instrument future interviews with employees would enhance the understanding of the organisational culture and hence further improve the road map. Originality/value: The authors developed a practical and strategic roadmap for a Scottish packaging small- and medium-sized enterprise (SME) which can be used by other similar SMEs. The proposed LSS road map can be replicated and/or adapted for companies in their application of LSS. The methodology by which this study's road map was designed can be used as a guide in the development of further CI road maps.